2018
DOI: 10.4143/crt.2017.013
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of HuR Inhibits the Progression of Esophageal Cancer through Interleukin-18

Abstract: PurposeThe purpose of this study was to investigate the effect of human antigen R (HuR) downregulation and the potential target genes of HuR on the progression of esophageal squamous cell carcinoma (ESCC).Materials and MethodsIn this study, a proteomics assay was used to detect the expression of proteins after HuR downregulation, and a luciferase assay was used to detect the potential presence of a HuR binding site on the 3’-untranslated region (3'-UTR) of interleukin 18 (IL-18). In addition, colony formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 28 publications
3
25
0
Order By: Relevance
“…Yu et al [51] recently showed that the RNA-binding protein ELAVL1 promotes bladder cancer progression by competitively binding to the long noncoding HOTAIR with MIR1-1HG. Similarly, Xu et al [52] found that downregulation of ELAVL1 inhibits the progression of esophageal cancer through IL18. Moreover, Badawi et al [53] demonstrated that silencing of the mRNA-binding protein ELAVL1 increases the sensitivity of colorectal cancer cells to ionizing radiation through upregulation of CASP2 (caspase2).…”
Section: Discussionmentioning
confidence: 87%
“…Yu et al [51] recently showed that the RNA-binding protein ELAVL1 promotes bladder cancer progression by competitively binding to the long noncoding HOTAIR with MIR1-1HG. Similarly, Xu et al [52] found that downregulation of ELAVL1 inhibits the progression of esophageal cancer through IL18. Moreover, Badawi et al [53] demonstrated that silencing of the mRNA-binding protein ELAVL1 increases the sensitivity of colorectal cancer cells to ionizing radiation through upregulation of CASP2 (caspase2).…”
Section: Discussionmentioning
confidence: 87%
“…Recently, a similar study also indicated that HuR protein and mRNA levels were higher in esophageal cancer tissues than in adjacent tissues [62]. The downregulation of HuR significantly inhibited cell proliferation and migration, and the mechanism may be related to the expression of HuR regulating matrix metalloproteinase 2 (MMP2), MMP9, and vimentin [62]. In addition, the overexpression of HuR leads to the increased stability of survivin mRNA and protein expression in esophageal cancer cells, which in turn regulates tumor cell apoptosis and promotes tumor growth [63].…”
Section: Hur and Esophagealmentioning
confidence: 82%
“…Multivariate analysis showed that cytoplasmic HuR expression is an independent prognostic factor for esophageal cancer and that its expression is associated with low survival rates in esophageal cancer [61]. Recently, a similar study also indicated that HuR protein and mRNA levels were higher in esophageal cancer tissues than in adjacent tissues [62]. The downregulation of HuR significantly inhibited cell proliferation and migration, and the mechanism may be related to the expression of HuR regulating matrix metalloproteinase 2 (MMP2), MMP9, and vimentin [62].…”
Section: Hur and Esophagealmentioning
confidence: 90%
“…Downregulation of UQCRC2 in CADH18 overexpressed glioma cell lines, partly reversed the inhibition of invasion/migration ability and chemoresistance . Xu et al . investigated the impact of human antigen R on the progression of esophageal squamous cell carcinoma (ESCC).…”
Section: Discovery Of Potential Drug Targetsmentioning
confidence: 99%